2021
DOI: 10.1007/s13201-021-01546-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of ground water quality index using remote sensing and GIS techniques

Abstract: Water is a vital and widely spread component required for sustaining the life. Groundwater is vastly valuable source and it is extremely beneficial for the human beings. But, the toxic elements release from sources such as industries, landfills as well as non-point causes of pollution such as pesticides and fertilizer from the past year showed high levels of pollution in ground water, hence this is very crucial for evaluating the water quality not only for it’s existing usage, but also a its capacity to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…However, the Chaju river may transport little calcium-bearing mineral water on its course as a result, it has soft water at Tukure (29mg/L). Hard water doesn’t have a serious health impact but is not forever good for bathing, laundering, and washing, however, its lower value is excellent in preventing pipe corrosion [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the Chaju river may transport little calcium-bearing mineral water on its course as a result, it has soft water at Tukure (29mg/L). Hard water doesn’t have a serious health impact but is not forever good for bathing, laundering, and washing, however, its lower value is excellent in preventing pipe corrosion [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the mapping in the form of a spatial map will describe the water quality found in the entire study area [7]. In this study, groundwater quality mapping of each contaminant parameter will be IOP Publishing doi:10.1088/1755-1315/1169/1/012019 3 obtained based on observations over 5 years.…”
Section: Groundwater Quality Mappingmentioning
confidence: 99%
“…Knowing the distribution of groundwater quality in urban cities is an informative tool in the form of a geographic information system (GIS) as an effective way to represent and analyze spatial data on water resources [5,6]. So that the mapping results in the form of a spatial map will describe the water quality categories found in the entire study area [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the investigations conducted using GIS combined with hydrochemical methodologies to identify the sources of groundwater pollution are beneficial for monitoring groundwater quality 12 . Numerous studies on using GWQI and GIS for groundwater quality assessment have been reported in the literature [14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%